2012
DOI: 10.1016/j.atherosclerosis.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Immune-modulation by polyclonal IgM treatment reduces atherosclerosis in hypercholesterolemic apoE−/− mice

Abstract: Poly-IgM treatment reduced aortic and accelerated carotid atherosclerosis in apoE-/- mice in association with increased anti-oxLDL IgG titers, and reduced number and proliferative function of splenic CD4(+) T cells. Our study identifies a novel athero-protective and immunomodulatory role for non-immune polyclonal IgM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 18 publications
2
30
1
1
Order By: Relevance
“…In summary, this study showed that B-cell activity was differentially enhanced with EPA and DHA ethyl esters, Natural IgM suppresses the progression of atherosclerosis by clearance of oxidized low density lipoprotein and apoptotic cells ( 51 ). This is of value in select clinical populations, such as those with lupus, that have increased susceptibility to cardiovascular disease which is associated with low levels of IgM antibodies against phosphorylcholine ( 52, 53 ).…”
Section: Resultsmentioning
confidence: 88%
“…In summary, this study showed that B-cell activity was differentially enhanced with EPA and DHA ethyl esters, Natural IgM suppresses the progression of atherosclerosis by clearance of oxidized low density lipoprotein and apoptotic cells ( 51 ). This is of value in select clinical populations, such as those with lupus, that have increased susceptibility to cardiovascular disease which is associated with low levels of IgM antibodies against phosphorylcholine ( 52, 53 ).…”
Section: Resultsmentioning
confidence: 88%
“…In this regard, the former could explain why sequence homology dictates cross-reaction; the latter may be due to antigenic surfaces rather than sequence homology that controls cross-reactivity. 25 Although the precise role of anti-oxLDL IgG in atherosclerosis remains unclear, anti-oxLDL-IgM induced by C5aR peptide immunization presumably plays an atheroprotective role in this regard; Cesena et al 26 recently reported that polyclonal IgM reduces advanced spontaneous aortic atherosclerosis as well as injuryinduced accelerated carotid atherosclerosis in an ApoE −/− mouse model study. Interestingly, in the present study, C5a levels in the plasma and C5aR expression in the lymph nodes in C5aR-peptide-immunized mice remained the same, but the functions (macrophage activation and inflammatory cytokine production) requiring receptor ligand interaction were impaired after immunization of C5aR peptides.…”
Section: Discussionmentioning
confidence: 99%
“…9 In mice, many studies suggest IgM antibodies provide an important atheroprotective layer. [11][12][13][14][15] The specific effect of deleting IgM antibodies (rather than B cells in general) was first addressed by Lewis et al 16 Mice lacking soluble IgM (but not B cell surface IgM or other isotypes of antibodies) have increased atherosclerosis. 16 However, in a more recent study using soluble IgM (sIgM −/− )/Ldlr −/− mice, we demonstrated that the enhanced atherosclerosis was a result of IgE accumulation in the circulation because anti-IgE injections completely reversed the phenotype.…”
Section: Meet the First Author See P 198mentioning
confidence: 99%
“…44 In addition, passive transfer of polyclonal IgM reduces atherosclerosis in ApoE −/− mice. 12 However, in sIgM −/− Ldlr −/− mice, impaired clearance of IgE promotes atherosclerosis, rather than direct local effects of IgM deficiency. 17 Compared with sIgM −/− mice, Ldlr…”
Section: 44mentioning
confidence: 99%